(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In recent years, there has been an increase in the prevalence of malignant tumors of the rectum - colorectal cancer. The steady increase in the incidence and mortality of the population from colorectal cancer, the high percentage of locally advanced and metastatic forms make the diagnosis and treatment tactics of this large category of patients especially urgent. In the modern scientific literature there is a lot of data on rectal cancer, which makes up 2-10% of all malignant diseases, ranking 6-8 in frequency. Among malignant tumors of the gastrointestinal tract, it belongs to the 2nd - 3rd place [1].